SEASONAL CHANGE OF ALGAE IN THE TREATMENT FACILITIES OF PONDS IN BUKHARA - Мустафаева Мамлакат Исмаловна (Ecomind Press, 2025)
The problem of preserving the environment is currently focusing the attention of researchers. Rapid population growth, an increase in the area of irrigated agriculture and the development of industries and others led to an unprecedented use of water resources. Along with this, methods of biochemical treatment of wastewater from organic and other pollutants using activated sludge or biofilm have become universally recognized. Their use allows you to reduce the content of organic and other substances in wastewater